From the Halal-Haram Dichotomy to a Typology of Contextual Law: An Analysis of Fiqh Muamalah and Maqashid al-Shari'ah Regarding PayLater Services in Indonesia - Aim Aminulhaq; Siti Zubaidah; Syaikhoni (NALAR FIQH: Jurnal Hukum Islam, 2026)
The rapid growth of PayLater (Buy Now Pay Later/BNPL) services in Indonesia, particularly among Generation Z, has raised complex legal issues regarding their compliance with Sharia principles. This study aims to analyze the legal status of PayLater through an integrated approach combining fiqh muamalah and maqashid al-shariah, rather than simply categorizing it dichotomously as halal or haram. The study employs a normative legal method with a descriptive-analytical-comparative design, utilizing a document review of the terms and conditions of the four largest PayLater platforms (SPayLater, GoPay Later, Akulaku, and Kredivo), DSN-MUI Fatwa No. 117/DSN-MUI/II/2018, and POJK No. 32 of 2025, triangulated with secondary empirical data from OJK, Kredivo-KIC, and IdScore. The research results identified three dominant contractual models, bai' muajjal, murabahah, and hybrid qardh, with the hybrid qardh model proving to be the most problematic because it structurally replicates riba al-jahiliyyah. An analysis of maqashid al-shariah reveals that the use of PayLater has the potential to threaten hifz al-mal and hifz al-'aql, particularly given Generation Z's relatively low level of financial literacy and the platform's design, which encourages impulsive consumer behavior. Based on these findings, this study proposes a typological framework of three normative categories, conditional mubah, makruh, and haram, as a more proportionate evaluation tool. It also recommends strengthening DSN-MUI fatwas, ensuring cost transparency by the OJK, improving Islamic financial literacy, and developing competitive Sharia-compliant BNPL products to create a digital financing ecosystem aligned with the fundamental objectives of maqashid al-shariah.